Storage bag

The storage bag addresses the issue of odor transfer in conventional bags by using a laminated film structure with a gas barrier, oxygen absorbing resin, and deodorant-containing adhesive layer, achieving effective oxygen absorption and odor prevention.

JP2025060202AActive Publication Date: 2025-04-10KANAO CAPRAKEMICAL CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023170781
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-29
Publication Date
2025-04-10
Estimated Expiration
2043-09-29

AI Technical Summary

Technical Problem

Conventional storage bags with oxygen-absorbing resin layers can generate unpleasant odor components due to oxidation reactions, which can transfer to the stored contents.

Method used

A storage bag made of a laminated film with a substrate layer, a gas barrier layer, an oxygen absorbing resin layer containing an oxygen absorbing compound, and a thermally adhesive resin layer that contains a deodorant, effectively preventing odor transfer.

Benefits of technology

The storage bag achieves high gas barrier properties, effective oxygen absorption, and prevents the transfer of unpleasant odor components to the contents, ensuring excellent storage properties for various liquids and powders.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025060202000001_ABST
    Figure 2025060202000001_ABST
Patent Text Reader

Abstract

To provide a practical storage bag which is high in gas barrier property, good in storage stability of contents, excellent in inside oxygen absorption function, and prevents the transfer of unpleasant odor components to the contents.SOLUTION: A laminated film F constituting a standing pouch is formed in such a manner of laminating a gas barrier layer 3 on (outside) a laminated film (stretched film) obtained by laminating a thermal adhesive resin layer (innermost layer) 7, an adhesive resin layer 6, and an oxygen absorbing resin layer 5 with an ester resin-based adhesive 4, and laminating a base material layer 1 on (outside) the gas barrier layer 3 with an ester resin-based adhesive 2.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a storage bag made of a synthetic resin film used as a storage bag for various liquids and powders such as food, medicines, cosmetics, and detergents. [Background technology]

[0002] Conventionally, three-sided bags, pouches, gusset bags, etc., made of a single synthetic resin film or a laminated film made of a plurality of synthetic resin films, have been widely used as storage bags for storing various liquids and powders such as food, medicines, cosmetics, detergents, etc. In recent years, in order to improve the preservation quality of stored foods, beverages, etc., storage bags have been developed that have an oxygen-absorbing resin layer containing an oxygen-absorbing resin having a carbon-carbon double bond to exhibit the function of absorbing oxygen inside (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP2006-334784A Summary of the Invention [Problem to be solved by the invention]

[0004] However, as described in Patent Document 1, an oxygen-absorbing resin having a carbon-carbon double bond absorbs (consumes) the oxygen inside by reacting with oxygen (oxidation reaction) at the carbon-carbon double bond. Therefore, in a storage bag provided with an oxygen-absorbing resin layer, the oxidation reaction can generate unpleasant odorous components, which can then be transferred to the contents.

[0005] The object of the present invention is to provide a practical storage bag which overcomes the problems associated with conventional storage bags such as those described in Patent Document 1 above, has high gas barrier properties, provides good storage stability for the contents, has excellent internal oxygen absorption capabilities, and prevents the transfer of unpleasant odorous components to the contents. [Means for solving the problem]

[0006] Among the present inventions, the invention described in claim 1 is a storage bag made of a laminated film made of synthetic resin, characterized in that the laminated film is a laminated film having a base layer made of a thermoplastic resin, a gas barrier layer for reducing oxygen permeability, an oxygen absorbing resin layer containing an oxygen absorbing compound, and a heat adhesive resin layer made of a heat adhesive resin that melts at a temperature of 80 to 200°C.

[0007] The invention described in claim 2 is characterized in that, in the invention described in claim 1, the oxygen-absorbing compound is an oxygen-absorbing synthetic resin (hereinafter referred to as oxygen-absorbing resin).

[0008] The invention described in claim 3 is the invention described in claim 1, characterized in that the thermal adhesive resin layer contains a deodorant.

[0009] The invention described in claim 4 is the invention described in claim 2, characterized in that the oxygen-absorbing resin is mainly composed of a mixed resin of a compound having a carbon-carbon double bond and an ethylene-vinyl alcohol copolymer.

[0010] The invention described in claim 5 is the invention described in claim 1, characterized in that the deodorant contains zeolite as a main component.

[0011] The invention described in claim 6 is characterized in that, in the invention described in claim 1, an adhesive resin layer containing an acid-modified polyolefin resin is provided between the oxygen absorbing resin layer and the thermal adhesive resin layer. Effect of the Invention

[0012] The storage bag described in claim 1 has high gas barrier properties, can block oxygen from the outside, and can effectively prevent oxygen from being supplied to the stored contents, and the oxygen absorbing resin layer located inside the gas barrier layer can effectively absorb the oxygen inside, so that the stored contents have good preservation properties. Furthermore, the heat-adhesive resin layer located on the innermost side makes it easy to manufacture and easy to seal after filling with the contents, and can effectively prevent odorous components generated in the oxygen absorbing resin layer from being transferred to the contents. Therefore, the storage bag described in claim 1 can be suitably used as a storage bag for various liquids and powders such as food, medicine, cosmetics, and detergents.

[0013] In the storage bag described in claim 2, since the oxygen-absorbing resin layer is made of an oxygen-absorbing resin, the oxygen inside can be absorbed more effectively, and therefore the storage stability of the stored contents is very good.

[0014] The storage bag described in claim 3 has a thermal adhesive resin layer containing a deodorizer, so that the deodorizer can absorb the odorous components generated when the oxygen-absorbing resin layer absorbs oxygen inside, thereby more effectively preventing the odorous components from being transferred to the contents.

[0015] The storage bag described in claim 4 is made of an oxygen-absorbing resin whose main component is a mixed resin of a compound having a carbon-carbon double bond and an ethylene-vinyl alcohol copolymer, and has excellent oxygen absorption function.Since the oxygen-absorbing resin can absorb the oxygen inside very effectively, the contents stored therein have extremely good preservation properties.

[0016] The storage bag described in claim 5 contains a deodorizer whose main component is zeolite and has excellent deodorizing function, so that it can effectively absorb odors emitted by the stored contents, thereby preventing the transfer of odorous components to the contents with greater accuracy.

[0017] The storage bag described in claim 6 has an adhesive resin layer containing an acid-modified polyolefin resin between the oxygen-absorbing resin layer and the thermal adhesive resin layer, and the peel strength of the interface between the oxygen-absorbing resin layer and the thermal adhesive resin layer is high, so that the bag is less likely to break even if it is dropped with the contents stored inside. [Brief description of the drawings]

[0018] [Figure 1] 4 is an explanatory diagram showing a cross-sectional view of a laminated film constituting a storage bag. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] The storage bag of the present invention is characterized in that it is formed from a laminated film having a base layer made of a thermoplastic resin, a gas barrier layer for reducing oxygen permeability, an oxygen absorbing resin layer containing an oxygen absorbing compound, and a heat adhesive resin layer made of a heat adhesive resin that melts at a temperature of 80 to 200°C.

[0020] The base layer of the laminated film may be a single layer or a laminate of multiple layers, and may be a polyethylene terephthalate (PET) film, a polybutylene terephthalate (PBT) film, a polyamide (PA) film, a polyethylene naphthalate (PEN) film, a polyacrylonitrile (PAN) film, a polycarbonate (PC) film, a polyimide (PI) film, a polyolefin film, etc. Among these, the use of a polyolefin film, a polyethylene terephthalate film, or a polyamide film is preferable because it can be produced at low cost and has good resistance to bag rupture, and a polyamide film is more preferable.

[0021] The gas barrier layer imparts high water vapor barrier properties and gas barrier properties to the storage bag in order to prevent the enclosed contents from coming into contact with moisture and oxygen. As the gas barrier layer, a deposition film in which a metal or metal oxide is deposited on a metal foil or a resin film can be used. As the metal foil, an aluminum foil or the like can be used, and the thickness thereof can be set to 5 to 20 μm. As the deposition film, a biaxially oriented polyethylene terephthalate (VMPET) having an aluminum deposition layer or a silica deposition layer, a biaxially oriented polypropylene (VMOPP) having an aluminum deposition layer or a silica deposition layer, or the like can be suitably used.

[0022] On the other hand, the oxygen-absorbing resin layer needs to be formed by a resin (base resin) containing an oxygen-absorbing compound, and as such an oxygen-absorbing compound, an oxygen-absorbing resin that itself exhibits oxygen absorption properties or an oxygen absorbent other than a resin can be used. As the oxygen-absorbing resin, a resin that absorbs oxygen by utilizing an oxidation reaction, such as polyamides such as polybutadiene, polyisoprene, polypropylene, ethylene-carbon oxide copolymer, 6-nylon, 12-nylon, and metaxylylenediamine nylon, to which organic acid salts containing transition metals such as cobalt, rhodium, and copper, and photosensitizers such as benzophenone, acetophenone, and chloroketones are added as oxidation catalysts, and a resin having oxygen barrier properties such as an ethylene-vinyl alcohol copolymer, polyamide, polyvinylidene chloride resin, polyvinyl alcohol, and fluororesin can be suitably used. Among these oxygen-absorbing resins, it is preferable to use an ethylene-vinyl alcohol copolymer or a modified product thereof, since the oxygen-absorbing resin layer has a very good oxygen-absorbing function. It is particularly preferable to use a saponified copolymer obtained by saponifying an ethylene-vinyl acetate copolymer having an ethylene content adjusted to 20 to 60 mol% (preferably, 25 to 50 mol%) to a degree of saponification of 96 mol% or more (preferably, 99 mol% or more).

[0023] In addition, it is preferable to use a mixed resin of a compound having a carbon-carbon double bond (i.e., an unsaturated compound) and an ethylene-vinyl alcohol copolymer as the oxygen absorbing resin, or a resin mainly composed of the mixed resin (i.e., a resin containing 50% by mass or more), since this improves the oxygen absorbing function of the oxygen absorbing resin layer. When adopting such a configuration, the unsaturated compound can be preferably a polydiene such as polybutadiene, polyisoprene, polychloroprene, poly(2-ethylbutadiene), or poly(2-butylbutadiene) that is polymerized mainly at the 1,4-position such as 1,4-polybutadiene, or a ring-opening metathesis polymer of a cycloolefin such as polyoctenylene, polypentenylene, or polynorbornene. Note that compounds having a carbon-carbon double bond only in an aromatic ring are not preferable. Furthermore, among these unsaturated compounds, it is preferable to use a thermoplastic resin having a carbon-carbon double bond substantially only in the main chain (i.e., a thermoplastic resin in which the carbon-carbon double bonds present in the main chain account for 90% or more of the total carbon-carbon double bonds in the molecule, and the carbon-carbon double bonds present in the side chain account for less than 10% of the total carbon-carbon double bonds in the molecule), since the oxygen absorbing resin layer has a very good oxygen absorbing function, and it is particularly preferable to use polyoctenylene. In addition, the amount of the unsaturated compound in the mixed resin of the unsaturated compound and the ethylene-vinyl alcohol copolymer is not particularly limited, but is preferably 10 to 90% by mass. If the amount of the unsaturated compound is less than 10% by mass, the oxygen absorbing resin layer will not exhibit a sufficient oxygen absorbing function, which is not preferable, and if the amount of the unsaturated compound is 90% by mass or more, the peel strength between the oxygen absorbing resin layer and other layers may be reduced, which is not preferable. It is more preferable that the amount of the unsaturated compound in the ethylene-vinyl alcohol copolymer is 25 to 75% by mass.

[0024] On the other hand, as oxygen absorbents other than resins, those having a function as a photocatalyst, such as titanium dioxide, tungsten oxide, zinc oxide, cerium oxide, strontium titanate, potassium niobate, etc. Among them, titanium dioxide is preferred because it is certified as a food additive and is inexpensive, and anatase type titanium dioxide (or a titanium dioxide with a high ratio of anatase type) is preferred because it can exhibit high oxygen absorption properties.

[0025] Furthermore, the resin (base resin) that contains these oxygen-absorbing compounds (i.e., oxygen-absorbing resins or oxygen absorbents) is not particularly limited, and examples thereof include olefin-based resins such as polyethylene (low density, medium density, and high density), linear low-density polyethylene, isotactic polypropylene, ethylene-propylene copolymers, polybutene-1, polymethylpentene-1, ethylene-butene-1 copolymers, propylene-butene-1 copolymers, ethylene-propylene-butene-1 copolymers, ethylene-vinyl acetate copolymers, ion-crosslinked olefin copolymers (ionomers), and blends thereof; polystyrene-based resins such as polystyrene, styrene-butadiene copolymers, styrene-isoprene copolymers, and ABS resins; thermoplastic polyesters such as polyethylene terephthalate, polybutylene terephthalate, and polytetramethylene terephthalate; and polycarbonates, which can be used alone or in combination of two or more.

[0026] The amount (addition amount) of the oxygen-absorbing compound in the resin (base resin) is not particularly limited, but when the oxygen-absorbing compound is an oxygen-absorbing resin, it is preferably 10 to 90% by mass. If the amount of the oxygen-absorbing resin is less than 10% by mass, the oxygen-absorbing resin layer will not exhibit sufficient oxygen absorption function, which is not preferable, and if the amount of the oxygen-absorbing resin is 90% by mass or more, the peel strength between the resin and other layers may be reduced, which is not preferable. The amount of the oxygen-absorbing resin in the resin is more preferably 25 to 75% by mass.

[0027] On the other hand, when the oxygen absorbing compound is an oxygen absorbent other than a resin, the blending amount (addition amount) of the oxygen absorbent in the resin (base resin) is preferably 1 to 10 mass %. If the blending amount of the oxygen absorbing resin is less than 1 mass %, the oxygen absorbing resin layer will not exhibit sufficient oxygen absorbing function, which is not preferable, and if the blending amount of the oxygen absorbent is 10 mass % or more, the oxygen absorbing function will be saturated, which is uneconomical, and the oxygen absorbing resin layer will be colored due to the oxygen absorption of the oxygen absorbent, which is not preferable. The blending amount of the oxygen absorbent in the resin is more preferably 4 to 7 mass %.

[0028] On the other hand, as the thermal adhesive resin layer (i.e., sealant layer), a sealant film made of a polyolefin resin such as polyethylene (low density, medium density, or high density), linear low density polyethylene, isotactic polypropylene, ethylene-propylene copolymer, etc. In addition, it is also possible to use a sealant film containing a resin derived from biomass (polyolefin resin, etc.).

[0029] Furthermore, the above-mentioned heat-adhesive resin layer can contain a deodorant. As such a deodorant, a porous material such as activated carbon, crystalline zeolite (aluminosilicate), silica gel, activated clay, etc., which physically adsorbs odorous components into pores to achieve a deodorant effect (so-called deodorant), can be suitably used. Among them, the use of zeolite (particularly high-silica zeolite with a silica content of 60% by mass or more) is particularly preferable, since it effectively adsorbs odorous components generated by the oxidation reaction in the oxygen-absorbing resin layer, thereby effectively preventing the odorous components from transferring to the contents.

[0030] In addition, the layer structure of the laminated film constituting the storage bag according to the present invention is not particularly limited, but it is preferable that the substrate layer, the gas barrier layer, the oxygen absorbing resin layer, and the heat adhesive resin layer are laminated in this order from the outside. In addition, when the oxygen absorbing resin layer and the heat adhesive resin layer are adjacent to each other, it is preferable to provide an adhesive resin layer made of acid-modified polyolefin or the like between these layers. It is particularly preferable to use maleic anhydride-modified polyolefin (particularly maleic anhydride-modified polyethylene) obtained by modifying polyolefin with maleic anhydride as the acid-modified polyolefin, since the peel resistance of the interface between the oxygen absorbing resin layer and the heat adhesive resin layer is high. In addition, as described above, when an adhesive resin layer made of acid-modified polyolefin or the like is provided between the oxygen absorbing resin layer and the heat adhesive resin layer, it is also possible to interpose it between the oxygen absorbing resin layer and the heat adhesive resin layer by co-extrusion of the resins constituting these layers.

[0031] In addition, in the laminated film constituting the storage bag according to the present invention, it is preferable that the base material layer and the gas barrier layer, and the gas barrier layer and the oxygen absorbing resin layer are bonded by an adhesive, respectively. As such adhesives, various adhesives such as ester resin-based adhesives and urethane resin-based adhesives can be used, and are not particularly limited, but it is preferable to use an ester resin-based adhesive, since it increases the peel resistance of the interface between the layers. In addition, the laminated film constituting the storage bag according to the present invention is not limited to those consisting of only the base material layer, the gas barrier layer, the oxygen absorbing resin layer, and the heat-adhesive resin layer, but can also include a printing layer, a functional layer, a surface coating layer, etc.

[0032] On the other hand, the thickness of the laminated film constituting the storage bag according to the present invention is not particularly limited, but is preferably 40 to 250 μm, and more preferably 110 to 180 μm, in terms of storage performance for the contents, bag rupture resistance, etc. Furthermore, the shape of the storage bag is not particularly limited, and various shapes such as two-sided bag, three-sided bag, pouch, gusset bag, etc. are possible, and although not particularly limited, a standing pouch is preferable because it can be filled with a large amount of contents and has good productivity. EXAMPLES

[0033] The storage bag according to the present invention will be described in more detail below based on examples. However, the present invention is not limited to the embodiments described herein and can be modified as appropriate without departing from the spirit of the present invention.

[0034] <Oxygen impermeability> The standing pouches manufactured in the Examples and Comparative Examples were sealed (sealed by heat sealing the upper edge without putting any contents inside) and left at room temperature for 30 days. The oxygen percentage after that was measured using an oxygen monitor OXY-1 manufactured by Presenns, and the values ​​were used to evaluate the pouches into the following three stages. ○: Oxygen fraction is less than 5% △: Oxygen fraction is 5% or more and less than 15% ×: Oxygen fraction is 15% or more

[0035] <Odor of contents> Water (ion-exchanged water) was placed inside the standing pouches manufactured in the Examples and Comparative Examples, and the top edge was heat-sealed to seal. The water-containing storage bag was then heated at 80°C for 3 minutes to boil the water, and the storage bag was then left to cool at room temperature for 1 week. The cooled storage bag was then opened, and the taste of the water was examined, and the taste and odor of the water were evaluated using the following 3-point scale (the average of the evaluation results of 3 trials by 3 subjects was calculated). ○: No unpleasant odor or taste △: Slightly strange odor or taste ×: Unusual odor or taste

[0036] <Seal strength (drop resistance)> Water (300cc) was poured into the standing pouches produced in the examples and comparative examples, and the top edge of the standing pouch was then heat-sealed to seal it. The water-filled standing pouch was then dropped freely from a height of 120cm onto a concrete floor with the bottom facing the floor, and the standing pouch was visually evaluated for any breakage after the drop. Twenty standing pouches of the same shape were formed in both the examples and comparative examples, and each of these standing pouches was evaluated for breakage. The same test was also performed on the standing pouches that had been cooled in an atmosphere of 10°C for 24 hours after being filled with water (300cc) and sealed, and the seal strength after boiling was also evaluated. ◎: Of the 20 pouches, none of the standing pouches were broken. ○: One or two of the 20 standing pouches were broken. △: Of 20, 3 or 4 standing pouches were broken. ×: 5 or more of the standing pouches were broken out of 20.

[0037] [Example 1] Each of the following resins (a) to (c) was melted at a temperature of 90°C in a co-extruder, co-extruded from a three-layer T-die in a mass ratio of 1:1:4, wound around a drum-shaped take-up machine (chill roll) adjusted to a temperature of 20°C, cooled and solidified, and taken up to obtain a three-layer unstretched film composed of laminated layers of each of the resins (a) to (c). (a) A mixed resin (resin for forming an oxygen absorbing resin layer) obtained by mixing a mixed resin of an ethylene-vinyl alcohol copolymer and a compound having a carbon-carbon double bond (unsaturated compound) (E105 manufactured by Kuraray Co., Ltd.) with an ethylene-vinyl alcohol copolymer (not mixed with an unsaturated compound, AP461B manufactured by Kuraray Co., Ltd.) in a ratio of 70:30 (mass ratio). (b) A mixed resin (resin for forming a thermal adhesive resin layer) made by mixing polyethylene and maleic anhydride-modified polyethylene in a ratio of 50:50 (mass ratio) (c) Linear low-density polyethylene (resin for forming adhesive resin layer)

[0038] The unstretched film thus obtained was then stretched 3.5 times in the longitudinal direction between rolls having different peripheral speeds at a temperature of 70°C, and then stretched 4.0 times in the transverse direction in an oven adjusted to a temperature of 80°C, thereby obtaining a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm.

[0039] Furthermore, an ester resin-based adhesive was applied to the surface of the oxygen-absorbing resin layer side of the stretched film obtained as described above (i.e., a stretched film having a three-layer laminate structure), and a silica-vapor-deposited polyethylene terephthalate film (biaxially stretched film) having a predetermined thickness (about 12 μm) was adhered to the applied surface to form a gas barrier layer. Further, an ester resin-based adhesive was applied to the gas barrier layer, and a polyethylene terephthalate film (biaxially stretched film) having a predetermined thickness (about 15 μm) for forming a base layer was adhered to the applied surface, and a predetermined pressure was applied between nip rolls heated to 70°C to obtain a laminated film of Example 1 having a total thickness of about 93 μm. FIG. 1 is a schematic diagram showing the cross section of the obtained laminated film. In the laminated film F, a gas barrier layer 3 is laminated (on the outside) on a laminated film (stretched film) formed by laminating a thermal adhesive resin layer (innermost layer) 7, an adhesive resin layer 6, and an oxygen absorbing resin layer 5 with an ester resin-based adhesive 4 (thickness: approximately 3.0 μm), and a base material layer 1 is laminated (on the outside) on the gas barrier layer 3 with an ester resin-based adhesive 2 (thickness: approximately 3.0 μm).

[0040] Then, using the obtained laminated film (using the thermal adhesive resin layer 7 as the innermost layer), a standing pouch having a predetermined size (length x width = 150 mm x 100 mm) was produced, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength (drop resistance)) were evaluated by the above-mentioned evaluation method. The evaluation results of the properties of the standing pouch of Example 1 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0041] [Example 2] An unstretched film having a three-layer structure in which layers made of the resins (a), (b), and (d) were laminated was formed in the same manner as in Example 1, except that the resin for forming the adhesive resin layer melt-extruded from the co-extruder was changed to the following resin (d). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, thereby obtaining a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm. (d) Linear low-density polyethylene containing 2% by mass of zeolite

[0042] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer, and the laminated film of Example 2 having a total thickness of approximately 93 μm was obtained by applying pressure while heating.

[0043] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 2 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0044] [Example 3] An unstretched film having a three-layer structure in which layers made of the resins (a), (b), and (e) were laminated was formed in the same manner as in Example 1, except that the resin for forming the adhesive resin layer melt-extruded from the co-extruder was changed to the following resin (e). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, thereby obtaining a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm. (e) Linear low-density polyethylene containing 5% by mass of zeolite

[0045] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer, and the laminated film of Example 3 having a total thickness of approximately 93 μm was obtained by applying pressure while heating.

[0046] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 3 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0047] [Example 4] An unstretched film having a three-layer structure in which layers made of the resins (a), (b), and (f) were laminated was formed in the same manner as in Example 1, except that the resin for forming the adhesive resin layer melt-extruded from the co-extruder was changed to the following resin (f). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, thereby obtaining a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm. (f) Linear low-density polyethylene containing 10% by mass of zeolite

[0048] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer and pressed under heating to obtain a laminated film of Example 4 having a total thickness of approximately 93 μm.

[0049] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 4 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0050] [Example 5] An unstretched film having a three-layer structure in which layers made of the resins (g), (b), and (c) were laminated was formed in the same manner as in Example 1, except that the resin for forming the oxygen-absorbing resin layer to be melt-extruded from the co-extruder was changed to the following resin (g). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, thereby obtaining a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm. (g) A mixed resin of an ethylene-vinyl alcohol copolymer and a compound having a carbon-carbon double bond (unsaturated compound) (E105 manufactured by Kuraray Co., Ltd.) and an ethylene-vinyl alcohol copolymer (not mixed with unsaturated compounds, AP461B manufactured by Kuraray Co., Ltd.) in a ratio of 90:10 (mass ratio).

[0051] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer, and the laminated film of Example 5 having a total thickness of approximately 93 μm was obtained by applying pressure while heating.

[0052] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 4 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0053] [Example 6] An unstretched film having a three-layer structure in which layers made of the resins (g), (b), and (e) were laminated was formed in the same manner as in Example 5, except that the resin for forming the adhesive resin layer to be melt-extruded from the co-extruder was changed to the above-mentioned resin (e) (i.e., linear low-density polyethylene with 5% by mass of zeolite added). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, to obtain a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm.

[0054] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer and pressed under heating to obtain a laminated film of Example 6 having a total thickness of approximately 93 μm.

[0055] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 6 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0056] [Example 7] An unstretched film having a three-layer structure in which layers made of the resins (h), (b), and (c) were laminated was formed in the same manner as in Example 1, except that the resin for forming the oxygen-absorbing resin layer to be melt-extruded from the co-extruder was changed to the following resin (h). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, thereby obtaining a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm. (h) A mixed resin of an ethylene-vinyl alcohol copolymer and a compound having a carbon-carbon double bond (unsaturated compound) (E105 manufactured by Kuraray Co., Ltd.) and an ethylene-vinyl alcohol copolymer (not mixed with unsaturated compounds, AP461B manufactured by Kuraray Co., Ltd.) in a ratio of 50:50 (by mass).

[0057] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer, and the laminated film of Example 7 having a total thickness of approximately 93 μm was obtained by applying pressure while heating.

[0058] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 7 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0059] [Example 8] An unstretched film having a three-layer structure in which layers made of the resins (h), (b), and (e) were laminated was formed in the same manner as in Example 7, except that the resin for forming the adhesive resin layer to be melt-extruded from the co-extruder was changed to the above-mentioned resin (e) (i.e., linear low-density polyethylene with 5 mass% zeolite added). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, to obtain a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm.

[0060] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer and pressed under heating to obtain a laminated film of Example 8 having a total thickness of approximately 93 μm.

[0061] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 8 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0062] [Example 9] A gas barrier layer was formed by adhering an alumina (aluminum oxide) vapor-deposited polyethylene terephthalate film (thickness: approximately 12 μm) to the surface of the oxygen-absorbing resin layer side of the stretched film obtained in the same manner as in Example 3 (i.e., a stretched film having a three-layer laminated structure) using the same ester resin-based adhesive as in Example 1, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer in the same manner as in Example 1, and the laminated film of Example 9 having a total thickness of approximately 93 μm was obtained by applying pressure while heating.

[0063] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 9 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0064] [Example 10] A gas barrier layer was formed by adhering an aluminum foil (thickness: approximately 7.0 μm) to the surface of the oxygen-absorbing resin layer side of a stretched film obtained in the same manner as in Example 3 (i.e., a stretched film having a three-layer laminate structure) using the same ester resin-based adhesive as in Example 1, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer in the same manner as in Example 1, and the laminated film of Example 10 having a total thickness of approximately 88 μm was obtained by applying pressure while heating.

[0065] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 10 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0066] [Example 11] A gas barrier layer was formed by adhering a silica-vapor-deposited polyethylene terephthalate film to the surface of the oxygen-absorbing resin layer side of a stretched film obtained in the same manner as in Example 3 (i.e., a stretched film having a three-layer laminate structure, the adhesive resin layer being made of resin (e)) in the same manner as in Example 1, and then a nylon film (thickness = approximately 15 μm) for forming a base layer was adhered to the gas barrier layer with the same ester resin-based adhesive as in Example 1. Further, by applying heat and pressure in the same manner as in Example 1, a laminated film of Example 12 having a total thickness of approximately 93 μm was obtained.

[0067] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 11 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0068] [Example 12] A gas barrier layer was formed by adhering the same aluminum foil (thickness = approximately 7.0 μm) as in Example 10 to the surface of the oxygen-absorbing resin layer side of a stretched film obtained in the same manner as in Example 3 (i.e., a stretched film having a three-layer laminate structure) using the same ester resin-based adhesive as in Example 1, and then adhering a nylon film for forming a base layer onto the gas barrier layer in the same manner as in Example 11, and applying pressure while heating to obtain a laminated film of Example 10 with a total thickness of approximately 88 μm.

[0069] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 12 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0070] [Example 13] A gas barrier layer was formed by adhering a silica-vapor-deposited polyethylene terephthalate film to the surface of the oxygen-absorbing resin layer side of the stretched film obtained in the same manner as in Example 3 (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1, and then a biaxially oriented polypropylene film (thickness = approximately 15.0 μm) for forming a base layer was adhered to the gas barrier layer with the same ester resin-based adhesive as in Example 1. Further, by applying heat and pressure in the same manner as in Example 1, a laminated film of Example 13 having a total thickness of approximately 93 μm was obtained.

[0071] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Example 13 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0072] [Comparative Example 1] A stretched film (i.e., a stretched film having a three-layer laminate structure) obtained in the same manner as in Example 3 was subjected to adhesion of a polyethylene terephthalate film for forming a base layer using an ester resin-based adhesive in the same manner as in Example 1, without forming a gas barrier layer on the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure). The laminated film had a total thickness of approximately 78 μm and was obtained as Comparative Example 1 by applying heat and pressure to the surface of the stretched film.

[0073] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Comparative Example 1 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0074] [Comparative Example 2] An unstretched film having a three-layer structure in which layers made of the resins (i), (b), and (e) were laminated was formed in the same manner as in Example 3, except that the resin for forming the oxygen-absorbing resin layer to be melt-extruded from the co-extruder was changed to the following resin (i: non-oxygen-absorbing resin). The unstretched film was stretched in the longitudinal and transverse directions in the same manner as in Example 1, thereby obtaining a stretched film having a three-layer laminate structure and a thickness of approximately 60 μm. (i) Linear low-density polyethylene

[0075] Thereafter, a silica-vapor-deposited polyethylene terephthalate film was adhered to the surface of the oxygen-absorbing resin layer side of the stretched film (i.e., a stretched film having a three-layer laminate structure) in the same manner as in Example 1 to form a gas barrier layer, and a polyethylene terephthalate film for forming a base layer was adhered onto the gas barrier layer and pressed under heating to obtain a laminated film of Comparative Example 2 having a total thickness of approximately 93 μm.

[0076] Using the obtained laminated film, a standing pouch was produced in the same manner as in Example 1, and the properties of the standing pouch (i.e., oxygen impermeability, odor of contents, and seal strength) were evaluated by the above-mentioned evaluation methods. The evaluation results of the properties of the standing pouch of Comparative Example 2 are shown in Table 1 together with the properties of the laminated film, which is the constituent material.

[0077] [Table 1]

[0078] From Table 1, it can be seen that the standing pouches of Examples 1 to 13 all had good oxygen impermeability, odor of the contents, and seal strength. In contrast, the standing pouch of Comparative Example 1 had poor oxygen impermeability and odor of the contents, and the standing pouch of Comparative Example 2 had poor odor of the contents. [Industrial Applicability]

[0079] Since the storage bag of the present invention has excellent effects as described above, it can be suitably used as a member for storing and packaging various substances. [Explanation of symbols]

[0080] F··Laminated Film 1...Base material layer 2...Adhesive layer 3. Gas barrier layer 4...Adhesive layer 5. Oxygen absorbing resin layer 6...Adhesive resin layer 7...Thermoadhesive resin layer

Claims

1. A storage bag made of a synthetic resin laminate film, The laminated film is A base layer made of a thermoplastic resin; A gas barrier layer for reducing oxygen permeability; An oxygen absorbing resin layer containing an oxygen absorbing compound; A storage bag comprising a laminated film having a heat-adhesive resin layer made of a heat-adhesive resin that melts at a temperature of 80 to 200°C.

2. 2. The storage bag according to claim 1, wherein the oxygen-absorbing compound is an oxygen-absorbing synthetic resin.

3. 2. The storage bag according to claim 1, wherein the oxygen absorbing resin layer contains a deodorant.

4. 3. The storage bag according to claim 2, wherein the oxygen-absorbing synthetic resin is mainly composed of a mixed resin of a compound having a carbon-carbon double bond and an ethylene-vinyl alcohol copolymer.

5. 4. The storage bag according to claim 3, wherein the deodorizing agent is mainly composed of zeolite.

6. The storage bag according to any one of claims 1 to 5, characterized in that an adhesive resin layer containing an acid-modified polyolefin resin is provided between the oxygen absorbing resin layer and the thermal adhesive resin layer.

Citation Information

Patent Citations

  • Oxygen adsorbable multilayered structure and packaging container

    JP2006334784A